Radiation Sounds Marshallese Music and Nuclear Silences - Schwartz, Jessica A. (Duke University Press, 2021)
Jessica A. Schwartz examines the seventy-five years of Marshallese music developed in response to the United States' nuclear weapons testing on their homeland, showing how Marshallese singing practices make heard the harmful effects of US nuclear violence.